Identification of Anti-staphylococcal and Anti-biofilm Compounds by Repurposing the Medicines for Malaria Venture Pathogen Box - Bhandari, Vasundhra; Chakraborty, Shalini; Brahma, Umarani; Sharma, Paresh (Frontiers in Cellular and Infection Microbiology, 2018)
There has been an alarming increase in infections caused by antimicrobial-resistant pathogens. These infections are responsible for more than half a million deaths globally each year. Staphylococcus aureus is one of the deadliest bacterial pathogen responsible for nosocomial and community acquired infections. The open-access Pathogen Box (PBox) provides a potential platform to identify new treatment options against antibiotic-resistant bacteria by repurposing it. In this study, we have screened the PBox library comprised of 400 compounds to identify novel anti-staphylococcal compounds. In vitro antimicrobial screening using S. aureus isolates, ATCC 29213 (methicillin-sensitive) and ATCC 700699 (methicillin-resistant) revealed 13 compounds which showed highly potent antibacterial activity against both planktonic and biofilm state. The 13 compounds were not found cytotoxic to mouse macrophage cell line, RAW264.7. Out of the 13 compounds, only MMV687251 and MMV676477 revealed structural similarity with vancomycin by comparing their atomic pair fingerprints using Tanimoto coefficient method. The structural similarities may indicate similar mode of action like vancomycin for the two compounds. Our result showed that PBox compounds offer a promising lead for the development of new anti-Staphylococcal treatment options.